A framework of space–time continuous models for algorithm design in swarm robotics - Hamann, Heiko; Wörn, Heinz (Swarm Intelligence)
Designing and analyzing self-organizing systems such as robotic swarms is a challenging task even though we have complete knowledge about the robot’s interior. It is difficult to determine the individual robot’s behavior based on the swarm behavior and vice versa due to the high number of agent–agent interactions. A step towards a solution of this problem is the development of appropriate models which accurately predict the swarm behavior based on a specified control algorithm. Such models would reduce the necessary number of time-consuming simulations and experiments during the design process of an algorithm. In this paper we propose a model with focus on an explicit representation of space because the effectiveness of many swarm robotic scenarios depends on spatial inhomogeneity. We use methods of statistical physics to address spatiality. Starting from a description of a single robot we derive an abstract model of swarm motion. The model is then extended to a generic model framework of communicating robots. In two examples we validate models against simulation results. Our experience shows that qualitative correctness is easily achieved, while quantitative correctness is disproportionately more difficult but still possible.

Sensomotorik: Kreuzbandverletzung hinterläßt Spuren im Gehirn - Baumeister, Jochen (Sportverl Sportschad)

Influence of phasphatidylserine on cognitive performance and cortical activity after induced stress - Baumeister, Jochen; Barthel, T; Geiss, K.R.; Weiss, M (Nutr Neurosci)

Cortical activity of skilled performance in a complex sports related motor task - Baumeister, Jochen; Reinecke, K; Liesen, H; Weiss, M (Eur J Appl Physiol)

Changed cortical activity after anterior cruciate ligament reconstruction in a joint position paradigm: an EEG study - Baumeister, Jochen; Reinecke, K; Weiss, M (Scand J Med Sci Sports)

Der Alphabeta-Algorithmus für Spielbäume: Wie bringe ich meinen Computer zum Schachspielen? - Monien, Burkhard; Lorenz, Ulf; Warner, Daniel (Taschenbuch der Algorithmen)

Bürgschaft - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Eigentumsvorbehalt - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Garantievertrag - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Grundschuld - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Hypothek - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Kreditsicherheiten - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Nutzungspfand - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Pfand-/Faustpfand - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Pfandrech - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Schuldbeitritt auch Schuld(mit)übernahme - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

Sicherungsübereignung - Krimphove, Dieter (Das neue Lexikon der Betriebswirtschaftslehre)

On Faster Integer Calculations Using Non-arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (Unconventional Computing)

Dynamic Control of Animation Schemes for the Efficient 3D-Visualization of Material Flow Simulations - Laroque, Christoph; Fischer, Matthias; Dangelmaier, Wilhelm; Eikel, Benjamin (Industrial Simulation Conference (ISC 2008))
This paper describes a method for the animation of a large number of objects within a dynamic 3D visualization of a material flow simulation model. It uses key-frame based animation. The number of animated objects may grow constantly in complex simulation models, which might lead to an amount of animations that is too big to be computed in real-time. By the use of a dynamic adjustment, the presented algorithm prefers important animations. Less relevant animations are updated rarely, whereby the selection itself is taken by multiple indicators, e.g. the visible size of the animated object on the screen, in order to keep a good optical impression. Dependent on the computing power of the computer, the algorithm controls the animations in such a way, that the fluid visualization of a large number of objects is still possible. Though the algorithm is to be used within a material flow simulator, it is moreover implemented in a specific animation editor, which allows the design and control of animation schemes. It supports the use of grouping to allow the creation of hierarchical structures for complex animations in a fast and easy manner. The evaluation of the algorithm is proven by a test scene, consisting of tens of thousands animated objects.

Regelung von Animationen in Simulationen von hochdynamischen Fabrikszenen - Laroque, Christoph; Fischer, Matthias; Eikel, Benjamin (Augmented & Virtual Reality in der Produktentstehung)
Dieser Artikel beschreibt eine Methode zur Animation einer großen Anzahl von Objekten zur dynamischen 3D-Visualisierung eines Simulationsmodells mittels der Materialflusssimulation auf Basis von Schlüsselbildern. Die Anzahl zu animierender Objekte ist in komplexen Modellen zu groß, um alle Animationen flüssig darzustellen. Dynamisch abgestuft wählt das entwickelte Verfahren gezielt wichtige Animationen aus, weniger relevante Animationen werden entsprechend seltener animiert. Die Selektion der Animationen erfolgt nach der projizierten Größe der Objekte auf das Ausgabegerät, um einen guten optischen Eindruck beizubehalten. Angepasst an die Leistungsfähigkeit des Rechners wird das Verfahren so geregelt, dass die Visualisierung einer hohen Anzahl von Objekten in Echtzeit möglich bleibt. Das Verfahren ist in einem Editor prototypisch implementiert, mit dem Schlüsselbilder für Objekte erzeugt werden können. Das Gruppieren von Objekten wird erlaubt, so dass eine Hierarchie von Bewegungspfaden definierbar ist. Die Evaluierung der Methode wird mittels Testszenen durchgeführt, die aus mehreren zehntausend animierten Objekten bestehen.

Singular Coverings and Non-Uniform Notions of Closed Set Computability - Le Roux, Stéphane; Ziegler, Martin (Electronic Notes in Theoretical Computer Science)

Mobile Cooperative WLANs - MAC and Transceiver Design, Prototyping, and Field Measurements - Valentin, Stefan; Lichte, Hermann S.; Warneke, Daniel; Biermann, Thorsten; Funke, Rafael; Karl, Holger (2008 IEEE 68th Vehicular Technology Conference)

Integrating Multiuser Dynamic OFDMA into IEEE 802.11 WLANs - LLC/MAC Extensions and System Performance - Valentin, S.; Freitag, T.; Karl, Holger (2008 IEEE International Conference on Communications)

Network-Coding-Based Cooperative Transmission in Wireless Sensor Networks: Diversity-Multiplexing Tradeoff and Coverage Area Extension - Woldegebreal, Dereje H.; Karl, Holger (Lecture Notes in Computer Science)

Who Should Pay for Forwarding Packets? - Ackermann, Heiner; Briest, Patrick; Fanghänel, Alexander; Vöcking, Berthold (Internet Mathematics)
We present a game theoretic study of hybrid communication networks in which mobile devices can connect in an ad hoc fashion to a base station, possibly via a few hops using other mobile devices as intermediate nodes. The maximal number of allowed hops might be bounded with the motivation to guarantee small latency. We introduce hybrid connectivity games to study the impact of selfishness on this kind of infrastructure. Mobile devices are represented by selfish players, each of which aims at establishing an uplink path to the base station minimizing its individual cost. Our model assumes that intermediate nodes on an uplink path are reimbursed for transmitting the packets of other devices. The reimbursements can be paid either by a benevolent network operator or by the senders of the packets using micropayments via a clearing agency that possibly collects a small percentage as commission. These different ways to implement the payments lead to different variants of the hybrid connectivity game. Our main findings are: (1) If there is no constraint on the number of allowed hops on the path to the base station, then the existence of equilibria is guaranteed regardless of whether the network operator or the senders pay for forwarding packets. (2) If the network operator pays, then the existence of equilibria is guaranteed only if at most one intermediate node is allowed, i.e., for at most two hops on the uplink path of a device, but not if the maximal number of allowed hops is three or larger. (3) In contrast, if the senders pay for forwarding their packets, then equilibria are guaranteed to exist given any bound on the number of allowed hops. The equilibrium analysis presented in this paper gives a first game theoretical motivation for the implementation of micropayment schemes in which senders pay for forwarding their packets. We further support this evidence by giving an upper bound on the Price of Anarchy for this kind of hybrid connectivity games that is independent of the number of nodes, but only depends on the number of hops and the power gradient.

Systematic analysis of the synchronization of twin screw extruders - Kriegel, Nils-Peter (International Rubber Mixing Symposium)

Approximation of Environment Models for an Air Gap Adjustment System in a Hybrid Planning Context - Adelt, Philipp; Schmidt, Alexander; Esau, Natascha; Kleinjohann, Lisa; Kleinjohann, Bernd; Rose, Mirko (MSC2008)

Interval Optimization in a Hybrid Planner Context for an Air Gap Adaptation System - Esau, Natascha; Adelt, Philipp; Schmidt, Alexander; Rose, Mirko (AISM 2008. 3rd Asia International Symposium on Mechatronics)

Holistic Conceptual Design of Self-Optimizing Systems - Gausemeier, Jürgen; Kahl, Sascha; Zimmer, Detmar; Schmidt, Alexander (AISM 2008. 3rd Asia International Symposium on Mechatronics)

Integrating dynamic track sectioning into a hybrid planning infrastructure - Schmidt, Alexander; Adelt, Philipp; Esau, Natascha (International Conference on Instrumentation, Control and Information Technology)

Determination of Active Pattern during the Conceptual Design of Self-Optimizing Systems Demonstrated by an Air Gap Adjustment System - Gausemeier, Jürgen; Podlogar, Herbert; Donoth, Jörg; Zimmer, Detmar; Schmidt, Alexander (International Conference on Systems Engineering)

Dynamic optimization of track sectioning in mechatronic systems for a hybrid planner - Schmidt, Alexander; Esau, Natascha; Adelt, Philipp; Stern, Claudius (IEEE International Conference on Mechatronics and Automation)

Development of Self-Optimizing Systems. Domain-Spanning and Domain-Specific Models Exemplified by an Air Gap Adjustment System for Autonomous Vehicles - Henkler, Stefan; Hirsch, Martin; Kahl, Sascha; Schmidt, Alexander (Computers and Information in Engineering Conference, Parts A and B)

Defining Plan Metrics for Multi-Agent Planning Within Mechatronic Systems - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Vöcking, Henner; Donoth, Jörg (Computers and Information in Engineering Conference, Parts A and B)

Using Enviromental Models Approximated by Fuzzy Identification for Hybrid Planning of Mechatronic Systems - Schmidt, Alexander; Adelt, Philipp; Esau, Natascha; Kleinjohann, Lisa; Kleinjohann, Bernd (Computers and Information in Engineering Conference, Parts A and B)

Proceedings for the conceptual design of self-optimizing mechatronic systems - Gausemeier, Jürgen; Zimmer, Detmar; Donoth, Jörg; Pook, Sebastian; Schmidt, Alexander (DESIGN 2008, International Design Conference)

A Multi-Agent Planning Problem for the Coordination of Function Modules - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Vöcking, Henner

Conceptual Design of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Donoth, Jörg; Pook, Sebastian; Zimmer, Detmar; Schmidt, Alexander

Flatness-based Online Controller Reconfiguration - Osmic, Semir; Trächtler, Ansgar (34th Annual Conference of the IEEE Industrial Electronics Society (IECON 2008), IEEE IES)

Modeling the Process of Drying Stationary Objects inside a Tumble Dryer Using COMSOL Multiphysics - Zeineldin, Tarek (COMSOL Conference 2008)

Hybrid Planning and Hierarchical Optimization of Mechatronic Systems - Münch, Eckehard; Adelt, Philipp; Krüger, Martin; Kleinjohann, Bernd; Trächtler, Ansgar (Proceedings of the International Conference on Control, Automation and Systems (ICCAS))

Development and Control of a Quarter-Vehicle Testbed for a Fully Active X-by-Wire Demonstrator - Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (9th International Symposium on Advanced Vehicle Control (AVEC 2008))

Organization and Control of Autonomous Railway Convoys - Henke, Christian; Tichy, Matthias; Schneider, Tobias; Böcker, Joachim; Schäfer, Wilhelm (Proceedings of the 9th International Symposium on Advanced Vehicle Control, Kobe, Japan)

Self-optimization of an Active Suspension System Regarding Energy Requirements - Voecking, Henner; Trächtler, Ansgar (International Conference on Control, Automation and Systems 2008 (ICCAS))

Mechatronic Design and Implementation of an Active Suspension for an All-Terrain Tracked Vehicle - Illg, Igor; Tewes, Michael; Jäker, Karl-Peter; Trächtler, Ansgar (9th International Symposium on Advanced Vehicle Control (AVEC 2008))

Model-based Controller Design for the Paper Separation-Process in Automatic Teller Machines - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (The 9th International Conference on Motion and Vibration Control (Movic 2008))

Defining Plan Metrics for Multi-Agent Planning within Mechatronic Systems - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Voecking, Henner; Donoth, Jörg (ASME 2008 - International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))

The Active Guidance Module of a Rail-Bound Vehicle as an Application of Dependability Oriented Design in Self-Optimizing Systems - Sondermann-Wölke, Christoph; Müller, Thomas; Geisler, Jens; Trächtler, Ansgar; Böcker, Joachim (ASME 2008 - International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))

Multiobjective Optimization of Control Trajectories for the Guidance of a Rail-bound Vehicle - Geisler, Jens; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (Proc. 17th IFAC World Congress)

Tool Support for the Design of Self-Optimizing Mechatronic Multi-Agent Systems - Burmester, Sven; Giese, Holger; Münch, Eckehard; Oberschelp, Oliver; Klein, Florian; Scheideler, Peter (International Journal on Software Tools for Technology Transfer (STTT))